COVID-19 associated Kawasaki-like multisystem inflammatory syndrome in an adult female with oral, ophthalmic and cardiac manifestation, a case report - Talayeh Mirkarimi; Mohammad Salek (طب اورژانس ایران, 2023)
Kawasaki disease is an acute febrile disease with the vasculitis of small and medium vessels that mainly affects children under the age of five, usually occurring after a viral respiratory disease. During the coronavirus disease-19 (COVID-19) pandemic, a significant increase was reported in the number of children with symptoms similar to Kawasaki disease, which is known as a multi-system inflammatory syndrome in children (MIS-C). A Kawasaki-like disease is rare in adults, especially in the context of COVID-19. We hereby present the case of A 41 year old female patient presented with complaints of bleeding from the gums and red and watery eyes, high fever, sore throat, weakness, and lethargy. She mentioned a recent contact with a COVID-19 patient. Covid-19 was confirmed by a positive reverse transcription polymerase chain reaction (RT-PCR) test. Other lab tests and clinical manifestations revealed inflammatory phenomena that fully complied with multi-system inflammatory syndrome in adults (MIS-A) criteria. The patient was treated with a possible diagnosis of MIS-A in the context of COVID-19 and was discharged in good general condition. COVID-19 rarely presents in adults without clear respiratory symptoms and in the form of multisystem inflammatory syndrome (MIS-A). Due to the possibility of irreversible complications, MIS-A requires special attention and early diagnosis and treatment.